Legal Certainty in the Regulations Regarding the Prohibition of Notaries from Serving as Leader of Private Business Entities - Yuni Aisyatun Nailah; Amelia Sri Kusuma Dewi; Diah Aju Wisnuwardhani (International Journal of Business, Economics, and Social Development, 2025)
Legal certainty in a regulation will create order. If every individual or law enforcer can interpret a regulation properly and clearly, then a regulation will run as it should. One of the prohibitions stipulated in Article 17 paragraph (1) letter f UUJN is the prohibition for notaries to hold concurrent positions as leaders of private business entities. The concept of a leader in various types of private business entities covers a broad role, from strategic decision-making to operational management. Interpretations of who is considered a "leader" can vary depending on the structure and characteristics of the business entity. This ambiguity creates room for multiple interpretations in the implementation of the prohibition against notaries. The involvement of notaries in leadership positions can threaten their independence or create potential conflicts of interest. This provision contains significant ambiguity in the definition of "leader of a private business entity," thus creating legal ambiguity. Legal ambiguity occurs when a legal regulation does not provide a clear and detailed definition or provision regarding a concept or term used, thus creating difficulties in its application and interpretation. This ambiguity causes legal uncertainty that is contrary to the basic principles of the formation of laws and regulations.